An intronic single nucleotide polymorphism in the MUTYH gene is associated with increased risk for HCV-induced hepatocellular carcinoma - Sakurada, Akira; Miyanishi, Koji; Tanaka, Shingo; Sato, Masanori; Sakamoto, Hiroki; Kawano, Yutaka; Takada, Kohichi; Nakabeppu, Yusaku; Kobune, Masayoshi; Kato, Junji (Free radical biology & medicine, 2018)
The role of base excision repair genes in human hepatocarcinogenesis has not yet been explored. Here, we investigated relationships between variants of these genes and the risk of developing hepatocellular carcinoma (HCC). Nineteen tagging SNPs in base excision repair genes (including MUTYH, OGG1 and MTH1) were genotyped using iPLEX assays; one significant SNP was found and confirmed in Japanese patients with chronic hepatitis C (CHC) (n = 38 HCC and 55 controls). The effects of modifying the intronic variants were determined by luciferase assays. MUTYH-null mice were used to examine the involvement of oxidative stress and DNA repair enzymes in hepatocarcinogenesis. Significant associations were found for a single intron SNP (rs3219487) in the MUTYH gene. The risk of developing HCC in patients with A/A or G/A genotypes was higher than in those with the G/G genotype (OR = 9.27, 95% CI = 2.39 −32.1, P = 0.0005). MUTYH mRNA levels in both peripheral mononuclear cells were significantly lower in G/A or A/A genotyped subjects (P = 0.0157 and 0.0108, respectively). We found that −2000 in the MUTYH promoter region is involved in enhanced expression of MUTYH by insertion of a major allele sequence of rs3219487. Liver tumors were observed in MUTYH-null mice after 12 months´ high iron diet, but no tumors developed when dietary anti-oxidant (N-Acetyl-L-cysteine) was also provided. CHC patients with the rs3219487 adenine allele had a significantly increased risk of developing HCC. MUTYH-null mice with iron-associated oxidative stress were susceptible to development of liver tumors unless prevented by dietary anti-oxidants. [Display omitted] •We investigated relationships between variants of base excision repair genes in human hepatocarcinogenesis.•Chronic hepatitis C patients with the rs3219487 adenine allele had a significantly increased risk of HCC.•MUTYH-null mice with iron-associated oxidative stress were susceptible to development of liver tumors.